Early plurilingual foreign language teaching in mixed classrooms: Linguistic and metalinguistic predictors of foreign language development among majority-language and minority-language students in EFL classes. (August 2022) - Hopp, Holger; Thoma, Dieter; Kieseier, Teresa; Jakisch, Jenny; Sturm, Sarah
Abstract: In a pre-posttest control group study, we test how plurilingual foreign language teaching affects foreign-language development in 258 primary-school students learning English in Germany. We compare general proficiency development in a group of students experiencing plurilingual teaching versus a group having regular, target-language-only teaching over a six-month period. Further, we assess whether and how proficiency in previously-acquired languages and phonological awareness affect learning gains in the plurilingual group. At the group level, the findings show that plurilingual instruction does not yield systematic differences compared to regular English instruction. Majority-language and minority-language students show comparable learning gains in standardized tests of receptive and productive vocabulary and receptive grammar in English. Regression analyses identify phonological awareness as a predictor of learning gains in the context of plurilingual foreign language learning. Further interactions with language background suggest that both proficiency in previously-acquired languages and metalinguistic skills modulate early foreign language learning and should be addressed in the classroom. Highlights: Plurilingual FL teaching does not compromise proficiency development in the foreign language. In plurilingual FL teaching, majority-language and minority-language learners have comparable proficiency gains. Phonological awareness predicts learning gains in early plurilingual FL teaching.